Film based verification of calculation algorithms used for brachytherapy planning-getting ready for upcoming challenges of MBDCA - Zwierzchowski, Grzegorz; Bielęda, Grzegorz; Skowronek, Janusz; Mazur, Magdalena (Journal of Contemporary Brachytherapy, 2016)
Purpose: Well-known defect of TG-43 based algorithms used in brachytherapy is a lack of information about interaction cross-sections, which are determined not only by electron density but also by atomic number. TG-186 recommendations with using of MBDCA (model-based dose calculation algorithm), accurate tissues segmentation, and the structure’s elemental composition continue to create difficulties in brachytherapy dosimetry. For the clinical use of new algorithms, it is necessary to introduce reliable and repeatable methods of treatment planning systems (TPS) verification. The aim of this study is the verification of calculation algorithm used in TPS for shielded vaginal applicators as well as developing verification procedures for current and further use, based on the film dosimetry method. Material and methods : Calibration data was collected by separately irradiating 14 sheets of Gafchromic® EBT films with the doses from 0.25 Gy to 8.0 Gy using HDR 192Ir source. Standard vaginal cylinders of three diameters were used in the water phantom. Measurements were performed without any shields and with three shields combination. Gamma analyses were performed using the VeriSoft® package. Results : Calibration curve was determined as third-degree polynomial type. For all used diameters of unshielded cylinder and for all shields combinations, Gamma analysis were performed and showed that over 90% of analyzed points meets Gamma criteria (3%, 3 mm). Conclusions : Gamma analysis showed good agreement between dose distributions calculated using TPS and measured by Gafchromic films, thus showing the viability of using film dosimetry in brachytherapy.